MAPPING FINANCIAL POTENTIAL OF SMALL AND MEDIUM ENTERPRISES (SMEs) AND THE ECONOMIC SECTOR OF SERANG DISTRICT - Indri Arrafi Juliannisa; Tri Siswantini (School of Business, IPB University (SB-IPB), 2021)
The existence of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia is considered as an economic buffer for three main reasons: 1) better performance at producing a productive workforce; 2) productivity increase through investment and actively following changes in technology; and 3) flexibility advantage compared to large business. The number of human resources who have the potential to become SME actors in Serang District is currently quite large, and the industrial sector is a superior sector that provides the largest contribution to the GRDP of Serang District. The purposes of this study were to find out how to map the financial potential of SMEs in Serang District and how to grow and map the economic sector in Serang District. This study used quantitative and qualitative analysis techniques (mixed methods), focusing on field conditions and the community in the studied area. This study found things that could increase MSMEs' financial potential in Serang District, namely capital, licensing, and product quality and marketing. Based on LQ analysis, the agricultural sector's outputs could be exported and expand the trade market share in other countries. Besides, Serang District is located in quadrant 3, with five potential economic sectors that could be developed further. Other economic sectors' potentials could be explored by subsector and be developed further. Keywords: SME financial potential, regional economic potential, klassen typology, location quotient, regional economy